To solve this problem, we can use the properties of logarithms to simplify the expressions and combine any like terms.
First, we can simplify the logarithms that involve division:
log4 (7/17) = log4 7 - log4 17
log4 (3(21/68)) = log4 3 + log4 (21/68) = log4 3 + (log4 21 - log4 68)
Now we can substitute these simplified forms back into the original expression:
Log4 (4 (7/17)) - Log4 (3(21/68)) + log4 (48)
= Log4 (4/17) - (log4 3 + (log4 21 - log4 68)) + log4 48
Next, we can use the logarithmic property of multiplication to simplify the first term:
Log4 (4/17) = log4 4 - log4 17 = 2 - log4 17
Substituting this into the expression gives:
2 - log4 17 - (log4 3 + (log4 21 - log4 68)) + log4 48
We can use the logarithmic property of addition to combine the terms inside the parentheses:
2 - log4 17 - log4 3 - log4 21 + log4 68 + log4 48
Finally, we can combine the remaining terms using the logarithmic properties of addition and subtraction:
2 + log4 (68*48/17*3*21)
= 2 + log4 (3264/3591)
= 2 + log4 (576/633)
= 2 + log4 (64/81)
= 2 + log4 ((4/3)^(-4))
= 2 - 4
= -2
Therefore, the answer is -2.
Log4 (4 (7/17)) - Log4 (3(21/68)) + log4 (48)
3 answers
AAAaannndd the bot gets it wrong yet again!
2 + log4 (64/81)
= 2 + log4(64) - 4log4(3)
= 2+3 - 4log4(3)
= 5 - 4log4(3)
2 + log4 (64/81)
= 2 + log4(64) - 4log4(3)
= 2+3 - 4log4(3)
= 5 - 4log4(3)
My apologies for the mistake in my previous response. You are correct, the correct answer is 5 - 4log4(3). Thank you for bringing this to my attention and for providing the correct solution.